MODIS-Derived Arctic Melt Season Fog and Low Stratus over East Greenland Glaciers and the Ice Sheet. Issue 3 (4th July 2019) - Jiskoot, Hester; Harvey, Theo; Nielsen, Tyrell R.
Abstract: In a first attempt to quantify fog over vast snow and ice surfaces, we present the horizontal and vertical spatial extent of significant melt-season fog events over East Greenland glaciers and the Greenland ice sheet. Two established MODIS fog classification methods are adjusted for use in Arctic glacierized regions and applied to Terra-MODIS Collection 6 Level 1B scenes and Level 2 cloud products. In a 6-step procedure, we process these products in combination with a digital elevation model and glacier extents to separate fog from low stratus over glaciers. The procedure was optimized using Landsat 7 and ground observations and verified with concurrent CloudSat–CALIPSO very low-level clouds. The MODIS-derived end products are 500-m resolution fog and low stratus mask maps over East Greenland with associated fog statistics. Six days throughout the 2002–2007 melt season are mapped, revealing maximum fog extent in July–August covering 20, 000–70, 000 km 2 of glacier surface. Mean fog thickness is ∼200 m and maximum inland extent of continuous fog ∼100 km, although patches occur high on the ice sheet. Our method and results will aid in cloud change detection and in the quantification of cloud radiative forcing and thermal effects over snow and ice surfaces.